Vapor-liquid equilibrium measurements for the nitrogen + tetrafluoromethane system over a temperature range of (134.27 to 204.85) K - Yu, G.; Guo, K.; Sun, Biao (American Chemical Society, 2009)
The isothermal vapor-liquid equilibrium for nitrogen (N2) + tetrafluoromethane (CF4) system P, T, y data was measured at temperatures of (134.27, 143.57, 153.95, 162.70, 173.43, 185.33, 192.51, and 204.85) K, respectively. The measurements were made with vapor recirculation method, and the experimental results were correlated with the Peng-Robinson equation of state and the van der Waals mixing rule. Through an optimization, the interaction parameters at each temperature and the overall interaction parameter for the whole range of experimental data were obtained. The deviations between the correlated and measured vapor compositions were calculated and the data showed a good consistency. © 2009 American Chemical Society.